Overcoming challenges in the expanding RNG market: Strategies and policies for stakeholders in the US - Purswani, Sanjay; Norouzi, Omid (Energy nexus, 2024)
•Key challenges facing RNG developers, including feedstock supply, financing, and regulation.•Challenges related to different types of RNG feedstocks and the need for more infrastructure.•Importance of supportive policies and industry investment in promoting RNG adoption in the US.•Recommendations for expanding the Renewable Fuel Standard and implementing a national Low Carbon Fuel Standard program.•Potential of RNG as a sustainable alternative to fossil fuels and the importance of addressing challenges to meet increasing demand. This paper explores the challenges faced by developers of Renewable Natural Gas (RNG) projects in the US. RNG is gaining popularity as a sustainable alternative to fossil fuels, but it is facing significant obstacles in the market. One of the main challenges for RNG developers is obtaining a consistent and reliable supply of feedstocks, which is complicated by high production costs and the need for more infrastructure. The paper examines the various types of feedstocks used in RNG production, including agricultural waste, municipal solid waste, and wastewater treatment plant sludge. Each feedstock has its unique challenges, such as transportation costs, storage requirements, and processing technologies. Furthermore, RNG production requires significant capital investments, which can be challenging to secure, particularly for small and medium-sized enterprises. In addition to feedstock and financing challenges, RNG developers face regulatory hurdles. RNG projects are subject to various federal and state regulations, including the Renewable Fuel Standard (RFS) and state-level Low Carbon Fuel Standard (LCFS) programs. The RFS has limited RNG's growth potential due to its focus on corn-based ethanol, while the LCFS program varies from state to state, creating regulatory uncertainty for RNG project developers. Despite these challenges, stakeholders are taking steps to promote the adoption of RNG. Industry groups are advocating for supportive policies, RNG developers are investing in infrastructure and developing new technologies, and policymakers are exploring options for expanding the RFS and implementing a national LCFS program.